Manufacturing method of stainless steel bolts
The method improves creep resistance and deformation resistance of austenitic stainless steel bolts through heat treatment, shot peening, and sacrificial corrosion film application, ensuring effective fastening in magnetic environments.
Patent Information
- Application Number
- JP2020187354
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-10
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-11-10
AI Technical Summary
Stainless steel bolts made of austenitic stainless steel exhibit low creep resistance, leading to gradual deformation over time due to slow nitrogen and carbon movement at room temperature, which affects their ability to maintain axial force and properly fasten objects.
A manufacturing method involving heat treatment of austenitic stainless steel bolts at 400°C to 500°C for 15 to 60 minutes, followed by shot peening or blasting, application of a sacrificial corrosion film, and a friction coefficient stabilizer to improve creep resistance, fatigue life, and prevent corrosion.
The method enhances creep resistance, reduces deformation, increases tightening torque, and extends the period before axial force decreases to acceptable limits, while maintaining non-magnetic properties suitable for environments with strong magnetic fields.
Smart Images

Figure 0007603273000003 
Figure 0007603273000004 
Figure 0007603273000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a stainless steel bolt. [Background technology]
[0002] Conventionally, various methods have been proposed for manufacturing stainless steel bolts. For example, Patent Document 1 discloses a method for manufacturing a stainless steel bolt by forming an austenitic stainless steel material by cold forging or warm forging at 300°C or less. Stainless steel bolts made of austenitic stainless steel are non-magnetic, and therefore suitable for fastening objects used in environments where a strong magnetic force is applied (environments with a strong magnetic field). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2006-274295 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, it is known that stainless steel bolts have low creep resistance (easily subject to creep deformation). In particular, stainless steel bolts made of austenitic stainless steel are prone to room temperature creep. The reason is presumed to be that because austenitic stainless steel has a face-centered cubic (FCC) crystal structure, the migration speed of nitrogen (N) and carbon (C) in the material at room temperature is very slow, and the fixation of the transition by N and C is insufficient (see, for example, Creep Deformation Behavior of Stainless Steel at Room Temperature, Iron and Steel, Vol. 79, No. 1, pp. 98-104). For this reason, after fastening an object with a stainless steel bolt made of austenitic stainless steel, the stainless steel bolt gradually deforms (stretches) over time due to the tensile force, which is the reaction force from the fastened object, and the axial force of the stainless steel bolt may decrease. For this reason, it may be impossible to properly fasten an object for a long period of time with a stainless steel bolt made of austenitic stainless steel.
[0005] The present invention has been made in consideration of the above-mentioned current situation, and has an object to provide a method for manufacturing a stainless steel bolt that can improve the creep resistance (reduce creep deformation) of a stainless steel bolt made of austenitic stainless steel. [Means for solving the problem]
[0006] One aspect of the present invention includes a step of preparing a stainless steel bolt made of austenitic stainless steel and having a male thread formed therein, and a heat treatment step of heat treating the prepared stainless steel bolt at a temperature in the range of 400°C to 500°C. In the heat treatment step, the heat treatment time is within a range of 15 minutes or more and less than 60 minutes. This is a manufacturing method for stainless steel bolts.
[0007] In the manufacturing method of the stainless steel bolt described above, first, a stainless steel bolt made of austenitic stainless steel (e.g., SUS316L) and having a male thread formed therein is prepared. This stainless steel bolt can be obtained by a known method. For example, a cylindrical material made of austenitic stainless steel is subjected to a process such as forging to form a head and a shaft, and then a male thread is formed on the shaft by thread rolling to obtain the stainless steel bolt.
[0008] Furthermore, in the manufacturing method of the stainless steel bolt described above, the prepared stainless steel bolt is heat-treated at a temperature in the range of 400°C to 500°C. Specifically, for example, the stainless steel bolt is placed in a heating furnace adjusted to a temperature in the range of 400°C to 500°C for a predetermined period of time. By carrying out such heat treatment, it is possible to improve the creep resistance of the stainless steel bolt (reduce creep deformation). The reason for this is presumed to be that by heat-treating a stainless steel bolt made of austenitic stainless steel at a temperature in the range of 400°C to 500°C, nitrogen (N) and carbon (C) in the material can be moved around the dislocations and fixed in advance. As a result, it is presumed that the movement of N and C dislocations at room temperature is reduced in the stainless steel bolt that has been subjected to the heat treatment process, and creep resistance is improved.
[0009] However, heat treatment of stainless steel bolts at temperatures higher than 500°C is not preferred because it may cause sensitization (intergranular corrosion) or thermal deformation of the bolts. Therefore, the heat treatment temperature for stainless steel bolts is preferably set within the range of 400°C to 500°C. As described above, according to the above-mentioned manufacturing method, it is possible to improve the creep resistance (reduce creep deformation) of a stainless steel bolt made of austenitic stainless steel.
[0011] In the above-mentioned manufacturing method, in the heat treatment step, the stainless steel bolt is heat treated at a temperature in the range of 400°C to 500°C for a time in the range of 15 minutes to 60 minutes. By performing the heat treatment for 15 minutes or more, the creep resistance of the stainless steel bolt can be improved. However, the longer the heat treatment time, the longer the manufacturing time of the stainless steel bolt and the higher the manufacturing cost, so the heat treatment time is preferably limited to 60 minutes or less. Therefore, the heat treatment time for the stainless steel bolt is preferably within the range of 15 minutes to 60 minutes.
[0013] If the heat treatment is carried out for 60 minutes or longer, there is a risk that the material structure (crystal structure) of the bolt will change partially (which will change the material properties (magnetic properties)), so the heat treatment time is preferably less than 60 minutes.
[0014] Furthermore, any of the above-mentioned methods for manufacturing a stainless steel bolt may preferably be provided with a shot process for performing shot peening or shot blasting on the stainless steel bolt that has been subjected to the heat treatment process, and a sacrificial corrosion coating formation process for applying a sacrificial corrosion coating treatment liquid to the surface of the stainless steel bolt that has been subjected to the shot process and baking this at a temperature within a range of 300°C to 400°C to form a sacrificial corrosion coating on the surface of the stainless steel bolt.
[0015] In the above-mentioned manufacturing method, in the shot step, the stainless steel bolt that has been subjected to the above-mentioned heat treatment step is subjected to shot peening or shot blasting. This imparts compressive residual stress to the stainless steel bolt, thereby improving the fatigue life of the stainless steel bolt. Furthermore, this makes it easier for a sacrificial corrosion coating, which will be described later, to adhere to the surface of the stainless steel bolt.
[0016] Furthermore, in the above-mentioned manufacturing method, in the sacrificial corrosion coating formation step, a sacrificial corrosion coating treatment liquid is applied to the surface of the stainless steel bolt that has been subjected to the above-mentioned shot process, and this (the sacrificial corrosion coating treatment liquid applied to the surface of the stainless steel bolt) is baked at a temperature in the range of 300° C. to 400° C. to form a sacrificial corrosion coating on the surface of the stainless steel bolt. When a stainless steel bolt having such a sacrificial corrosion coating is used to fasten a fastened object, the sacrificial corrosion coating of the stainless steel bolt can be preferentially dissolved, thereby suppressing corrosion (galvanic corrosion) of the fastened object.
[0017] The sacrificial corrosion coating treatment liquid is a treatment liquid (paint) for forming a sacrificial corrosion coating on the surface of the stainless steel bolt, and the sacrificial corrosion coating treatment liquid applied to the surface of the stainless steel bolt is baked onto the surface of the stainless steel bolt to become a sacrificial corrosion coating. An example of the sacrificial corrosion coating is Geomet (trade name).
[0018] In the sacrificial corrosion coating formation process, the sacrificial corrosion coating treatment liquid applied to the surface of the stainless steel bolt is baked at a temperature in the range of 300° C. to 400° C. Baking at a temperature of 300° C. or higher can improve the adhesion of the sacrificial corrosion coating to the surface of the stainless steel bolt.
[0019] Furthermore, the higher the baking temperature of the sacrificial corrosion coating, the greater the release of the compressive residual stress imparted in the shot process during baking. Specifically, if the baking temperature is higher than 400°C, the release of the compressive residual stress imparted in the shot process becomes significant, and there is a risk that fatigue strength cannot be ensured. In contrast, in the above-mentioned sacrificial corrosion coating formation process, the baking temperature is set to 400°C or less, thereby reducing the release of the compressive residual stress imparted in the shot process. This makes it possible to improve the fatigue life of the stainless steel bolt.
[0020] Furthermore, the method for manufacturing the stainless steel bolt may be such that a friction coefficient stabilizer is applied to the surface of the stainless steel bolt after the sacrificial corrosion coating formation process and then dried to form a friction coefficient stabilizing coating.
[0021] By forming a friction coefficient stabilizing coating on the surface of a stainless steel bolt, the variation in the axial force of the stainless steel bolt can be reduced. This allows the tightening torque of the stainless steel bolt to be increased (and therefore the lower limit of the initial axial force can be increased), thereby increasing the margin for the decrease in axial force due to creep of the stainless steel bolt. Specifically, for example, the period during which the axial force of the stainless steel bolt decreases to the lower limit of the allowable range due to room temperature creep can be extended. An example of a friction coefficient stabilizer is ex Torquer (trade name).
[0022] Furthermore, in any of the above-mentioned methods for manufacturing a stainless steel bolt, the stainless steel bolt may be a stainless steel bolt for a railway vehicle.
[0023] In railway vehicles, stainless steel bolts made of austenitic stainless steel are often used, and the use of bolts with high creep resistance is required. In contrast, the above-mentioned manufacturing method can improve the creep resistance (reduce creep deformation) of stainless steel bolts made of austenitic stainless steel, and is therefore suitable as a manufacturing method for stainless steel bolts for railway vehicles. [Brief description of the drawings]
[0024] [Figure 1] FIG. 2 is a side view of the stainless steel bolt according to the embodiment. [Diagram 2] FIG. 1 is a diagram illustrating a creep test. [Diagram 3] FIG. 1 is a diagram showing the results of a creep test. [Figure 4] FIG. 1 is a correlation diagram between heat treatment temperature and yield stress. [Diagram 5] FIG. 1 is a correlation diagram between baking temperature and maximum compressive residual stress. [Figure 6] FIG. 1 is a correlation diagram between baking temperature and fatigue life. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] Next, an embodiment of the present invention will be described with reference to the drawings. Fig. 1 is a side view of a stainless steel bolt 10 according to the embodiment. The stainless steel bolt 10 is made of austenitic stainless steel and has a head 11 and a shaft 12. A male thread 13 is formed in the shaft 12.
[0026] The stainless steel bolt 10 made of austenitic stainless steel is a non-magnetic material and is therefore not easily affected by magnetic forces even in environments where strong magnetic forces are present (environments with strong magnetic fields). For this reason, the stainless steel bolt 10 of this embodiment is suitable for fastening objects used in environments where strong magnetic forces are present (environments with strong magnetic fields). The stainless steel bolt 10 of this embodiment is a stainless steel bolt for use in railway vehicles.
[0027] Here, a method for manufacturing the stainless steel bolt 10 according to this embodiment will be described. First, a stainless steel bolt 10 made of austenitic stainless steel (e.g., SUS316L) and having a male thread 13 formed therein is prepared. This stainless steel bolt 10 can be obtained by a known method. Specifically, for example, a cylindrical material made of austenitic stainless steel (e.g., SUS316L) is subjected to a process such as forging to form a head 11 and a shaft 12, and then a male thread 13 is formed on the shaft 12 by thread rolling, thereby preparing the stainless steel bolt 10 (see FIG. 1).
[0028] Next, in the heat treatment step, the prepared stainless steel bolt 10 is heat-treated at a temperature in the range of 400°C to 500°C for a predetermined time (for example, 15 minutes to 60 minutes). Specifically, the stainless steel bolt 10 is placed in a heating furnace (not shown) adjusted to a temperature in the range of 400°C to 500°C for a predetermined time (for example, 15 minutes to 60 minutes). By carrying out such heat treatment, the creep resistance of the stainless steel bolt 10 can be improved (creep deformation can be reduced). The reason for this is presumed to be that by heat-treating the stainless steel bolt 10 made of austenitic stainless steel at a temperature in the range of 400°C to 500°C for a predetermined time, nitrogen (N) and carbon (C) in the material can be moved around the dislocations and fixed. As a result, it is presumed that the movement of dislocations at room temperature is reduced in the stainless steel bolt 10 that has been subjected to the heat treatment step, and creep resistance is improved.
[0029] However, heat treating the stainless steel bolt 10 at a temperature higher than 500°C is not preferred because it may cause sensitization (intergranular corrosion) in the stainless steel bolt 10. Therefore, the heat treatment temperature for the stainless steel bolt 10 is preferably set within the range of 400°C to 500°C.
[0030] In addition, in the above-mentioned heat treatment step, the heat treatment time for the stainless steel bolt 10 is preferably within a range of 15 to 60 minutes. That is, in the heat treatment step, the stainless steel bolt 10 is preferably heat treated at a temperature within a range of 400°C to 500°C for a time within a range of 15 to 60 minutes. By heat treating the stainless steel bolt 10 for 15 minutes or more, the creep resistance of the stainless steel bolt 10 can be improved. However, the longer the heat treatment time, the longer the manufacturing time of the stainless steel bolt 10 and the higher the manufacturing cost, so the heat treatment time is preferably limited to 60 minutes or less. Therefore, the heat treatment time for the stainless steel bolt 10 is preferably within a range of 15 to 60 minutes.
[0031] Furthermore, in the above-mentioned heat treatment step, it is more preferable that the heat treatment time for the stainless steel bolt 10 is less than 60 minutes. This is because if the heat treatment of the stainless steel bolt 10 is performed for 60 minutes or more, there is a risk that a part of the material texture (crystal structure) of the stainless steel bolt 10 will change (thereby changing the material properties). Therefore, it is more preferable that the heat treatment time for the stainless steel bolt 10 is within the range of 15 minutes or more and less than 60 minutes.
[0032] Then, in the shot process, the stainless steel bolt 10 that has been subjected to the heat treatment process is subjected to shot peening or shot blasting. This imparts compressive residual stress to the stainless steel bolt 10, thereby improving the fatigue life of the stainless steel bolt 10. Furthermore, this makes it easier for a sacrificial corrosion film, which will be described later, to adhere to the surface of the stainless steel bolt 10.
[0033] Next, in the sacrificial corrosion coating formation process, a sacrificial corrosion coating treatment liquid is applied to the surface of the stainless steel bolt 10 that has been subjected to the shot blasting process, and this (the sacrificial corrosion coating treatment liquid applied to the surface of the stainless steel bolt 10) is baked at a temperature in the range of 300°C to 400°C. In this way, a sacrificial corrosion coating (not shown) is formed on the surface of the stainless steel bolt 10. When the stainless steel bolt 10 having such a sacrificial corrosion coating is used to fasten a fastened object, the sacrificial corrosion coating of the stainless steel bolt 10 can be preferentially dissolved, thereby suppressing corrosion (galvanic corrosion) of the fastened object.
[0034] The sacrificial corrosion coating treatment liquid is a treatment liquid (paint) for forming a sacrificial corrosion coating on the surface of the stainless steel bolt, and the sacrificial corrosion coating treatment liquid applied to the surface of the stainless steel bolt is baked onto the surface of the stainless steel bolt to become a sacrificial corrosion coating. In this embodiment, Geomet (trade name) is used as the sacrificial corrosion coating.
[0035] In the sacrificial corrosion coating formation process, the sacrificial corrosion coating treatment liquid applied to the surface of the stainless steel bolt 10 is baked at a temperature in the range of 300° C. to 400° C. Baking at a temperature of 300° C. or higher can improve the adhesion of the sacrificial corrosion coating to the surface of the stainless steel bolt 10.
[0036] Furthermore, the higher the baking temperature of the sacrificial corrosion coating, the greater the release of the compressive residual stress imparted in the shot process during baking. Specifically, if the baking temperature is higher than 400°C, the release of the compressive residual stress imparted in the shot process becomes significant, and there is a risk that fatigue strength cannot be ensured. In contrast, in the sacrificial corrosion coating formation process of this embodiment, the baking temperature is set to 400°C or less, thereby reducing the release of the compressive residual stress imparted in the shot process. This makes it possible to improve the fatigue life of the stainless steel bolt 10.
[0037] After that, a friction coefficient stabilizer is applied to the surface of the stainless steel bolt 10 that has been subjected to the sacrificial corrosion coating formation process, and then dried to form a friction coefficient stabilizing coating (not shown). This completes the stainless steel bolt 10 of this embodiment (see FIG. 1). In this embodiment, ex Torquer (trade name) is used as the friction coefficient stabilizer.
[0038] By forming a friction coefficient stabilizing coating on the surface of the stainless steel bolt 10, it is possible to reduce the variation in the axial force of the stainless steel bolt 10. This allows the tightening torque of the stainless steel bolt 10 to be increased (and therefore the lower limit of the initial axial force to be increased), thereby increasing the margin for the reduction in axial force due to creep of the stainless steel bolt 10. Specifically, for example, it is possible to lengthen the period during which the axial force of the stainless steel bolt 10 reduces to the lower limit of the allowable range due to room temperature creep.
[0039] <Creep test> Next, the creep test will be described. FIG. 2 is a diagram for explaining the creep test. FIG. 3 is a diagram showing the results of the creep test. First, the creep test will be described. As shown in FIG. 2, a cylindrical fastened object 30 was fastened using the stainless steel bolts 10 of Examples 1 to 4 and an iron nut 20. More specifically, using a known nut runner, the fastened object 30 was fastened by the stainless steel bolt 10 and the nut 20 at a predetermined tightening torque, aiming for the axial force of the stainless steel bolt 10 to be 95 kN.
[0040] A steel ground washer 41 is interposed between the head 11 of the stainless steel bolt 10 and one end 31 (the left end in FIG. 2) of the fastened object 30. A steel ground washer 42 is interposed between the nut 20 and the other end 32 (the right end in FIG. 2) of the fastened object 30. The fastened object 30 is made of a material equivalent to S50, has a hardness of HV400, and has a zinc-plated surface.
[0041] Four strain gauges (not shown) are provided on the outer peripheral surface of the fastened object 30. More specifically, the four strain gauges are provided at the center of the outer peripheral surface of the fastened object 30 in the axial direction (left and right direction in FIG. 2) of the fastened object 30, and are equally spaced in the circumferential direction. In this creep test, the output values of the four strain gauges provided on the outer peripheral surface of the fastened object 30 are obtained in the fastened state shown in FIG. 2, and the axial force of the stainless steel bolt 10 fastening the fastened object 30 is calculated based on the average value of the four obtained output values. Note that this creep test is performed in a room temperature environment (specifically, in a temperature environment in the range of 22°C to 23°C).
[0042] <Example 1> In Example 1, in the heat treatment step, the stainless steel bolt 10 was heat treated at a temperature of 400° C. for 15 minutes.
[0043] <Example 2> In Example 2, in the heat treatment step, the stainless steel bolt 10 was heat treated at a temperature of 450° C. for 15 minutes.
[0044] <Example 3> In Example 3, in the heat treatment step, the stainless steel bolt 10 was heat treated at a temperature of 500° C. for 15 minutes.
[0045] <Example 4> In Example 4, in the heat treatment step, the stainless steel bolt 10 was heat treated at a temperature of 500° C. for 60 minutes.
[0046] In this creep test, three stainless steel bolts 10 of each Example were prepared, and in each Example, the above-mentioned axial force was calculated for each of the three stainless steel bolts 10, and the average value of the three axial forces (hereinafter referred to as the average axial force) was obtained. Furthermore, in this creep test, for the stainless steel bolts 10 of each Example, the average axial force (kN) was first obtained at the time of fastening, and then the average axial force values of the stainless steel bolts 10 fastening the fastened object 30 were also obtained on the second day (i.e. the day after the day of fastening), the third day, the fourth day, the seventh day, the eighth day, the ninth day, the tenth day, the eleventh day, the fourteenth day, and the fifteenth day.
[0047] Then, the reduction rate of the average axial force after tightening (hereinafter, simply referred to as the axial force reduction rate) was calculated for the stainless steel bolt 10 of each example. More specifically, for the average axial force on each measurement day from the second day onwards, the ratio of the reduction amount from the average axial force at the time of tightening was calculated as the axial force reduction rate (%). The axial force reduction rate (%) was calculated using the following calculation formula. Axial force reduction rate (%) = {(average axial force at fastening - average axial force on each measurement day after fastening) / average axial force at fastening} x 100
[0048] In addition, in this creep test, a stainless steel bolt was prepared as Comparative Example 1, which differs from Example 1 only in that it was not subjected to a heat treatment process.The stainless steel bolt of Comparative Example 1 was also subjected to a creep test similar to that performed on the stainless steel bolt 10 of Examples 1 to 4 to determine the axial load reduction rate. The results of this creep test are shown in Figure 3.
[0049] As shown in FIG. 3, the stainless steel bolts 10 of Examples 1 to 4 had smaller values of the axial force reduction rate than the stainless steel bolt of Comparative Example 1. Specifically, in Comparative Example 1, the axial force reduction rate was 4% or more after 15 days, whereas in Examples 1 to 4, the axial force reduction rate was less than 4% after 15 days. That is, the stainless steel bolts 10 of Examples 1 to 4 were able to suppress the reduction in axial force after fastening compared to the stainless steel bolt of Comparative Example 1. It can be said that the smaller the axial force reduction rate, the better the creep resistance of the stainless steel bolt. Therefore, it can be said that the stainless steel bolts 10 of Examples 1 to 4 have better creep resistance than the stainless steel bolt of Comparative Example 1.
[0050] From the results of this creep test, it can be said that the creep resistance of the stainless steel bolt 10 can be improved by heat treating the stainless steel bolt 10 at a temperature in the range of 400°C to 500°C. However, if the heating temperature is too high, there is a risk of sensitization and a decrease in strength occurring in the stainless steel bolt 10, so it is preferable to limit the heating temperature to 500°C. Furthermore, from the results of this creep test, it can be said that the heat treatment time is preferably in the range of 15 minutes to 60 minutes.
[0051] <Cutting surface observation of stainless steel bolt 1> Next, stainless steel bolts 10 of samples 1 to 5 were prepared, and the shafts of these were cut in a direction perpendicular to the axial direction, and the cut surfaces were polished. Then, the cut stainless steel bolts 10 of each sample were immersed in a 10% oxalic acid solution and subjected to electrolytic corrosion treatment for 30 seconds to reveal the metal structure on the cut surface. The cut surfaces of the stainless steel bolts 10 of each sample were observed with a metallurgical microscope. The results are shown in Table 1.
[0052] Sample 1 is a stainless steel bolt 10 that has not been subjected to a heat treatment process, Sample 2 is the stainless steel bolt 10 of Example 3 (i.e., the stainless steel bolt 10 that has been subjected to a heat treatment process at a temperature of 500°C for 15 minutes), and Sample 3 is a stainless steel bolt 10 that has been subjected to a heat treatment process at a temperature of 500°C for 180 minutes.
[0053] Sample 4 is a stainless steel bolt 10 that has been subjected to a heat treatment process at a temperature of 700° C. for 15 minutes, and Sample 5 is a stainless steel bolt 10 that has been subjected to a heat treatment process at a temperature of 700° C. for 180 minutes.
[0054] [Table 1]
[0055] As a result of observing the cut surfaces, as shown in Table 1, the crystal grain boundaries were clearer in the cut surfaces of Sample 4 and Sample 5 compared to the cut surface of Sample 1, and sensitization (intergranular corrosion) had occurred. That is, in the stainless steel bolts (Samples 4 and 5) that had been subjected to the heat treatment process at a temperature of 700°C, which was higher than 500°C, sensitization (intergranular corrosion) had occurred as a result of the heat treatment, regardless of the heat treatment time.
[0056] On the other hand, the microstructural state of the cut surface of Sample 2 and Sample 3 was almost the same as that of Sample 1. That is, in the stainless steel bolts (Samples 2 and 3) that underwent a heat treatment process at a temperature of 500°C, no change was observed in the microstructural state of the stainless steel bolt before and after the heat treatment, regardless of the heat treatment time, and sensitization (intergranular corrosion) did not occur. From these results, it can be said that the heating temperature in the heat treatment step is preferably set to 500° C. or less.
[0057] <Observation of cut surface of stainless steel bolt 2> Furthermore, stainless steel bolts 10 of samples 6 to 10 were prepared, and the shafts of these were cut in a direction perpendicular to the axial direction, and the cut surfaces were polished. Then, the cut stainless steel bolts 10 of each sample were immersed in a 10% oxalic acid solution and subjected to electrolytic corrosion treatment for 30 seconds to reveal the metal structure on the cut surface. The results of observing the cut surfaces with a metallurgical microscope are shown in Table 2.
[0058] Sample 6 is a stainless steel bolt 10 that was not subjected to a heat treatment process, Sample 7 is the stainless steel bolt 10 of Example 1 (i.e., the stainless steel bolt 10 that was subjected to a heat treatment process at a temperature of 400°C for 15 minutes), and Sample 8 is the stainless steel bolt 10 of Example 2 (i.e., the stainless steel bolt 10 that was subjected to a heat treatment process at a temperature of 450°C for 15 minutes).
[0059] In addition, sample 9 is the stainless steel bolt 10 of Example 3 (i.e., the stainless steel bolt 10 subjected to a heat treatment process at a temperature of 500°C for 15 minutes), and sample 10 is the stainless steel bolt 10 of Example 4 (i.e., the stainless steel bolt 10 subjected to a heat treatment process at a temperature of 500°C for 60 minutes).
[0060] [Table 2]
[0061] As a result of observing the cut surface, as shown in Table 2, ferrite crystals were confirmed on the cut surface of the stainless steel bolt in Sample 10. That is, in the stainless steel bolt 10 that underwent a heat treatment process at a temperature of 500°C for 60 minutes, ferrite crystals were generated by the heat treatment process.
[0062] On the other hand, in the other samples 6 to 9, ferrite crystals were not observed on the cut surface of the stainless steel bolt 10. That is, in the stainless steel bolt 10 that had been subjected to a heat treatment process at a temperature in the range of 400°C to 500°C for less than 60 minutes, ferrite crystals were not observed, just like in the stainless steel bolt 10 that had not been subjected to a heat treatment process. From these results, it can be said that the heat treatment time in the heat treatment step is preferably less than 60 minutes.
[0063] <Tensile test> Several types of stainless steel bolts 10 were prepared with different heat treatment temperatures and heat treatment times in the heat treatment step, and a tensile test was performed on each of the stainless steel bolts 10 to measure the yield stress. The results are shown in Figure 4. Figure 4 is a correlation diagram between the heat treatment temperature in the heat treatment step and the yield stress of the stainless steel bolt. In Figure 4, the graph for the stainless steel bolt 10 with a heat treatment time of 15 minutes is shown by a solid line, and the graph for the stainless steel bolt 10 with a heat treatment time of 60 minutes is shown by a dashed line. In Figure 4, the data at a temperature of 20°C (i.e., room temperature) is the data for the stainless steel bolt 10 before the heat treatment step was performed.
[0064] As shown in FIG. 4, when the heat treatment temperature is 300° C. or higher, the yield stress is improved. Specifically, the yield stress of the stainless steel bolt 10 before the heat treatment was about 900 MPa, but by performing the heat treatment at 300°C or higher, the yield stress could be improved to 1000 MPa or higher. It can be assumed that if the yield stress of a stainless steel bolt is improved, the creep resistance will also be improved. Therefore, from the results of this test, it can be assumed that the creep resistance of the stainless steel bolt 10 will be improved by setting the heat treatment temperature in the heat treatment process to 300°C or higher.
[0065] <Baking temperature and compressive residual stress> Fig. 5 is a correlation diagram between the baking temperature of the sacrificial corrosion coating in the sacrificial corrosion coating formation process and the maximum compressive residual stress of the stainless steel bolt 10 after the sacrificial corrosion coating formation process. The compressive residual stress of the stainless steel bolt 10 is imparted in the shot step before the sacrificial corrosion coating formation process. In Fig. 5, the data for a baking temperature of 0°C is the maximum compressive residual stress of the stainless steel bolt 10 after the shot step and before the sacrificial corrosion coating formation process.
[0066] As shown in Figure 5, the higher the baking temperature, the greater the release of the compressive residual stress imparted in the shot process during baking. In particular, if the baking temperature is higher than 400°C, the release of the compressive residual stress becomes significant, and there is a risk that the fatigue strength of the stainless steel bolt 10 cannot be ensured. Therefore, the following tensile fatigue test was carried out to investigate the relationship between the baking temperature and the fatigue life of the stainless steel bolt 10. This is explained below.
[0067] <Tensile fatigue test> A plurality of stainless steel bolts 10 with different baking temperatures of the sacrificial corrosion coating in the sacrificial corrosion coating formation process were prepared, and a tensile fatigue test was performed to investigate the fatigue life of each stainless steel bolt 10. Specifically, a repeated tensile load in the axial direction was applied to each stainless steel bolt 10, and the number of repeated loads until each stainless steel bolt 10 broke was investigated.
[0068] Fig. 6 is a correlation diagram between the baking temperature of the sacrificial corrosion coating in the sacrificial corrosion coating formation process and the fatigue life (number of repeated loads) of the stainless steel bolt 10. The temperature on the horizontal axis of Fig. 6 is the baking temperature, and "none" indicates no baking, i.e., the stainless steel bolt 10 after the shot process and before the sacrificial corrosion coating formation process. The vertical axis of Fig. 6 is the number of repeated loads (×10 5 times) and represents the fatigue life.
[0069] As shown in Fig. 6, the higher the baking temperature, the shorter the fatigue life. In particular, when the baking temperature is set to 500°C (i.e., higher than 400°C), the decrease in fatigue life becomes significant. Therefore, in order to ensure the fatigue strength of the stainless steel bolt 10, it is preferable that the baking temperature of the sacrificial corrosion coating in the sacrificial corrosion coating formation step be 400°C or lower.
[0070] Although the present invention has been described above with reference to an embodiment, it goes without saying that the present invention is not limited to the above embodiment and can be modified as appropriate without departing from the spirit of the present invention. [Explanation of symbols]
[0071] 10 Stainless steel bolts 11 Head 12 Shaft 13 Male thread 20 Nut 30 Object to be fastened
Claims
1. A step of preparing a stainless steel bolt made of austenitic stainless steel and having a male thread formed thereon; A heat treatment step of heat treating the prepared stainless steel bolt at a temperature in the range of 400°C to 500°C, In the heat treatment step, the heat treatment time is within a range of 15 minutes or more and less than 60 minutes. Manufacturing method of stainless steel bolts.
2. A step of preparing a stainless steel bolt made of austenitic stainless steel and having a male thread formed therein; A heat treatment step of heat treating the prepared stainless steel bolt at a temperature in the range of 400°C to 500°C, a shot process of performing shot peening or shot blasting on the stainless steel bolt that has been subjected to the heat treatment process; and a sacrificial corrosion coating forming process for applying a sacrificial corrosion coating treatment liquid to the surface of the stainless steel bolt after the shot process and baking the liquid at a temperature in the range of 300°C to 400°C to form a sacrificial corrosion coating on the surface of the stainless steel bolt. Manufacturing method of stainless steel bolts.
3. A method for manufacturing a stainless steel bolt according to claim 2, A friction coefficient stabilizer is applied to the surface of the stainless steel bolt after the sacrificial corrosion coating formation process and then dried to form a friction coefficient stabilizing coating. Manufacturing method of stainless steel bolts.
4. A method for producing a stainless steel bolt according to any one of claims 1 to 3, The stainless steel bolt is a stainless steel bolt for railroad cars. Manufacturing method of stainless steel bolts.
Citation Information
Patent Citations
Production of high tensile strenght bolts
JP1978103923A
Production of stainless steel bolt and nut and its product
JP1984162224A
Stainless steel bolt
JP1986006209A
Production of high strength stainless steel bolt for structural use
JP1991193823A
Drill screw made of austenite group stainless steel and manufacture thereof
JP1992064705A
